Cotton cloth templated in situ encapsulation of sulfur into carbon fibers for lithium–sulfur batteries. Issue 4 (18th December 2020) - Raulo, Avinash; Gupta, Amit; Srivastava, Rajiv; Nandan, Bhanu
Abstract : For energy storage applications, sulfur was in situ synthesized and encapsulated inside carbon fibers by using waste cotton textiles as the fiber template. Abstract : An in situ encapsulation strategy for embedding sulfur within carbon (S@C) fiber through a sustainable and scalable route using waste cotton cloth as a fiber template, is developed. The S@C fibers with reasonably high sulfur content of ∼71% displayed promising electrochemical performance when employed as a cathode material for a lithium sulfur battery (LSB). The S@C fibers developed herein have the potential to be used as a promising cathode material for other sulfur-based batteries as well.